The Impact of Media/Technology on Rural and Urban Children to be Bilingual/ Multilingual - Hosen, Md. Sozib; Khatun, Mst. Tanna (International Journal of Language and Literary Studies, 2021)
This article will focus on the comparative study of the influence of media and technology on rural and urban children to be bilingual and multilingual. The study will also shed light on the importance of bilingualism and multilingualism. TV and YouTube are taken into account as tools of media and technology for implicit language learning. Children of 8-12 years are considered as samples of language learners. Data have been collected from a primary source through a questionnaire and interviews. The result of the research shows that there is a significant impact of watching different kinds of TV/YouTube programs (cartoons, movies, serials, reality shows) which are presented in foreign languages on children to be bilingual and multilingual though the results of the rural and urban area are significantly different. In the study, the researchers have found that children living in municipal area are more bilingual and multilingual compared to children living in rustic area.